PEMANFAATAN LIMBAH KULIT BUAH SEBAGAI BIO BATERAI BERBASIS STEM UNTUK MENINGKATKAN KETERAMPILAN PRAKTIKUM SISWA - Evi Wahyuni Kusuma Ningrum; Dody Rahayu Prasetyo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to develop learning media in the form of bio batteries from fruit peel waste based on the STEM (Science, Technology, Engineering, and Mathematics) approach to improve science students' practical skills. The study used the 4D model (Define, Design, Develop, Disseminate). The products developed were bio battery kits and STEM-based Student Worksheets (LKPD). The validation results showed that the developed media obtained a score of 92% from material experts and 96% from media experts. The trial was conducted on 32 grade VIII students with a pretest-posttest. The results showed an increase in the average score from 64.21 to 81.40 with a significance of 0.000 (p <0.05). Bio batteries from orange and pineapple peels produced the highest voltage and were able to turn on an analog wall clock. The response of students and teachers to the product was very positive. The STEM approach encouraged students to be more active in experiments.